54.8k views
2 votes
Which is a correct first step in solving the inequality -4(2x-1)>5-3x

2 Answers

5 votes
The correct first step of solving the inequality problem -4(2x-1)>5-3x is that

Expand -4(2x-1): -8x+4

You apply the distributive laws
a=4, b=2x, c=1
= -4x time 2x-(-4) time 1

Simplify -4 time 2x+4 time 1
Multiply the numbers: 4 time2=8
= -8x+4

Multiply the numbers: 4time1=4
= -8x+4

User Petermlm
by
4.3k points
1 vote

Answer:

Apply distributive property that's the first step.

Explanation:

The given inequality is


-4(2x-1)>5-3x

The first step we need to do is to apply distributive property to relase the binomial inside the parenthesis


-8x+4>5-3x

Then, we move all variables to the left side, and all constants to the right side


-8x+3x>5-4\\-5x>1

Now, we divide the inequality by -5, which changes the sign orientation


(-5x)/(-5) <(1)/(-5)\\ x<-(1)/(5)

Therefore, the solution is a set with all values less than -1/5. The graph attached shows this solution.

Which is a correct first step in solving the inequality -4(2x-1)>5-3x-example-1
User Chandramani
by
4.6k points